2016
DOI: 10.1159/000442611
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Acts as an Antidepressant by Inhibition of the Acid Sphingomyelinase/Ceramide System

Abstract: Background: Melatonin has been shown to have antidepressive effects. We tested whether melatonin inhibits the acid sphingomyelinase/ceramide system and mediates its antidepressive effects via inhibition of the acid sphingomyelinase and a reduction of ceramide in the hippocampus. Antidepressants such as amitriptyline and fluoxetine were previously shown to inhibit the acid sphingomyelinase/ceramide system, which mediates neurogenesis and behavioral changes induced by these drugs. Methods: The effect of melatoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…It was shown that 3-week daily treatment of 10 mg/kg BW melatonin prevented CORT-induced reduction in cell proliferation in the DG and reduced depression- and anxiety-like behavior of the mice in the forced swim test, open field test, and novelty suppressed feeding test [ 51 ]. The anti-depressive and neurogenetic effects of melatonin was potentially brought about by the inhibition of the acid sphingomyelinase/ceramide system as well as the decrease in vesicular monoamine transporter 2 (VMAT2) levels and increase in the monoamine oxidase A MAO-A levels in the hippocampus [ 52 , 53 ]. Using combination treatment of melatonin and citalopram (MLTCITAL), 14-day daily treatment of 2.57 mg/kg BW MLTCITAL promoted neurogenesis and reduced depression-like behavior in adult mice [ 54 ] ( Table 3 ).…”
Section: Melatonin and Depressionmentioning
confidence: 99%
“…It was shown that 3-week daily treatment of 10 mg/kg BW melatonin prevented CORT-induced reduction in cell proliferation in the DG and reduced depression- and anxiety-like behavior of the mice in the forced swim test, open field test, and novelty suppressed feeding test [ 51 ]. The anti-depressive and neurogenetic effects of melatonin was potentially brought about by the inhibition of the acid sphingomyelinase/ceramide system as well as the decrease in vesicular monoamine transporter 2 (VMAT2) levels and increase in the monoamine oxidase A MAO-A levels in the hippocampus [ 52 , 53 ]. Using combination treatment of melatonin and citalopram (MLTCITAL), 14-day daily treatment of 2.57 mg/kg BW MLTCITAL promoted neurogenesis and reduced depression-like behavior in adult mice [ 54 ] ( Table 3 ).…”
Section: Melatonin and Depressionmentioning
confidence: 99%
“…Thus, it has been previously shown that inhibition of the acid sphingomyelinase/ceramide systems prevents the effects of stress in the hippocampus [10,[25][26][27] and functions upstream of stress-activated kinases such as p38Kinase [25].…”
Section: Discussionmentioning
confidence: 99%
“…These observations are in accordance with the multiple results on NSC protection, proliferation, and differentiation both in vivo and in vitro (Table 1). Rat midbrain NSCs None Viability↑ dopaminergic differentiation (tyrosine hydroxylase↑), BDNF↑ GDNF↑ [110] Mouse NSCs from ganglionic eminence None Differentiation to neurons↑ in FBS-stimulated proliferation, but not in differentiation period [111] Murine induced pluripotent stem cells None Differentiation to NSCs↑ and further to neurons↑ PI3K/AKT signaling [112] Mouse hippocampal NSCs None Survival↑ differentiation↑ [113] NSCs from adult murine SVZ None Proliferation↑ differentiation↑; ERK/MAPK signaling [114,115] Rat adult hippocampal NSCs None Proliferation↑ phosphorylation of ERK1/2 andc-Raf [116] Mouse adult spinal cord NSPCs None Proliferation↑ PI3K/AKT signaling [117] Murine hippocampus in vivo None Neurogenesis↑ [118] Murine dentate gyrus in vivo None NeuN+ cells↑ DCX+ cells↑ [108,113,[119][120][121][122][123][124] Rat dentate gyrus in vivo Pinealectomy Neurogenesis↑ [125] Rat embryonal NSCs IL-18 Proliferation↑ differentiation↑ BDNF↑ GDNF↑ [126] Mouse embryonic cortical NSCs LPS Sox2 expression↑ PI3K/Akt/Nrf2 signaling [20] Mouse cortical NSCs in vitro Hypoxia Proliferation↑ differentiation to neurons↑ MT 1 dependence, pERK1/2↑ [19] Mouse embryonic cortical NSCs Hyperglycemia Proliferation↑ self-renewal↑ autophagy↓ [127] Murine dentate gyrus in vivo Corticosterone Attenuation of proliferation suppression [128] Rat adult hippocampal NSCs Dexamethasone Reversal of inhibition of nestin and Ki67 expression [129] Murine dentate gyrus in vivo Dexamethasone Attenuation of suppressed DCX expression [130] Murine dentate gyrus in vivo Cuprizone Restoration of Ki67+ proliferative cells and DCX+ NPCs; BNDF↑ [131] Murine dentate gyrus in vivo Scopolamine Restoration of Ki67+ proliferative cells and DCX+ NPCs [132] Murine dentate gyrus in vivo d-Galactose (aging model) Restoration of Ki67+ proliferative cells and DCX+ NPCs…”
Section: Neurogenesis From Nscs/nspcsmentioning
confidence: 99%